Mitochondrial quality control links two seemingly unrelated neurodegenerative diseases. Issue 10 (3rd October 2022) - Tang, Yinglu; Huang, Yunpeng; Wan, Zhihui; Zhou, Bing; Wu, Zhihao
Abstract: Despite certain overlapping clinical presentations, the two human neurodegenerative diseases pantothenate kinase-associated neurodegeneration (PKAN) and Parkinson disease (PD) have distinct genetic etiologies. During our work using Drosophila to study PKAN and PINK1-related PD, we found some common mitochondrial abnormalities in these two disease models, suggesting a potential link in pathogenesis between them. When we delve into their underlying mechanisms, mitochondrial quality control (MQC) stands at the crossroads. While overwhelming evidence suggests that mitochondrial dysfunction plays a role in the pathogenesis of many human neurodegenerative diseases, mitochondrial function is particularly important for PKAN and PD (some inherited PD cases) foretold by the nature of their causative genes. PKAN is caused by mutations in PANK2 (pantothenate kinase 2), the only PANK localized to mitochondria among the four human PANK isoforms. PANKs catalyze the initial step of de novo coenzyme A (CoA) synthesis. PKAN patients and disease models display disturbed mitochondrial functions, but its exact mechanism has not been clearly determined. Usually, damaged mitochondria are surveyed and eliminated by the MQC pathway. Two genes that have been found critical for PD, PINK1 (PTEN induced kinase 1) and PRKN (parkin RBR E3 ubiquitin protein ligase), are positioned at the center of MQC. If the MQC is normal, malfunctional mitochondria will usually be efficiently repaired. Thus, the accumulation of mitochondrial dysfunction in PKAN implies that its MQC mechanism is impaired. The question is, how? In a recent published work, we attempted to answer this question.